DIGI-TREE: Manajemen Digital Pohon untuk Edukasi, Rekreasi, dan Konservasi Berbasis Komunikasi Visual - Susenohaji, Susenohaji; Dhanias, Fitriana Rakhma; Sutawijaya, Bayu; Muhammad, Rifki; Nabila, Nabila (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Tree management and conservation in urban and rural areas is still dominated by conventional methods that limit access to information and community participation. This community service activity aims to implement DIGI-TREE, a QR code-based digital tree management system as a medium for environmental education and conservation. The implementation method was descriptive-applicative through system design, installation of QR codes on trees, provision of visual content in the form of infographics and educational videos, and assistance in the use of the system to the community. The results of the community service showed that DIGI-TREE made it easier for the community to access real-time tree information, increased understanding of the ecological functions of trees, and encouraged community involvement in environmental monitoring. Information presented visually has proven to be easier to understand than conventional media. Therefore, DIGI-TREE has the potential to become a technology-based community service model that supports participatory and sustainable tree management and environmental conservation.